Exploring 30 Years of Culturally Responsive Teaching in Higher Education: A Bibliometric Analysis - Sari, Ratna; Purwanto, Agung; Nurjayadi, Muktiningsih; Irwanto, Irwanto (International Journal of Multidisciplinary Research of Higher Education (IJMURHICA), 2026)
Culturally Responsive Teaching has become an essential pedagogical framework in higher education, affirming cultural diversity and fostering inclusive learning environments. Despite its growing relevance, the global intellectual structure and research patterns of Culturally Responsive Teaching remain underexplored. This study presents a bibliometric analysis of 726 Scopus-indexed documents published between 1995 and 2025. Microsoft Excel and Bibliometrix were used for performance indicators, while VOSviewer supported network visualization. Results indicate consistent growth in publications, with an average annual increase of 18.83%, reflecting sustained academic engagement. The United States leads in publication output and citation impact, followed by Australia and Canada, while developing regions remain underrepresented. The University of California is the most active institution, contributing 71 publications. Curriculum Inquiry emerges as a leading journal, publishing two highly cited articles with 520 citations. Geneva Gay’s seminal work is the most cited, receiving 514 citations, while Lorri J. Santamaría from the University of Auckland authored three papers with an h-index of 3. Keyword analysis highlights dominant themes such as “higher education,” “students,” “cultural competence,” and “cultural sustainability.” The implications of this study emphasize strengthening scholarship in underrepresented regions and fostering global collaboration, while offering practical insights for integrating Culturally Responsive Teaching into inclusive higher education reforms.